Timeline Events in Christian Mission in Africa - Onu, Ben (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The history of Christianity is a fascinating story of the manifestation of the finger of God in the affairs of mankind.  The church has passed through different stages of life, and â€œyet has hardly reached the period of full manhood in Christ Jesusâ€. Sequential presentation of church historical events seems to be â€œgenerally abandonedâ€.  Chronicling church history developments allows for better view of the progress made and the connectivity of events. This paper aims at presenting the key events in the growth and development of Christianity especially in Africa in its progressive order. It applies the chronological or annalistic approach to bring in the natural flow of events. This is carried out in five main streams for better appreciation and understanding.  The paper concludes that the arrival of missionaries of both the Reformation (Protestant) and Roman Catholic faith, and acceptability of the natives has given Christianity a strong hold in the African continent. Keywords: Timeline, events, Christian mission, Africa